A study on the temperature field of a bronze-bonded diamond wheel dressed using a laser/ultrasonic vibration combined method. (January 2017) - Yang, Zhibo; Zhang, Zhen; Liu, Aiju; Liu, Shian
Abstract : To solve problems in dressings for metal-bonded super-hard abrasive wheels, such as low efficiency and rapid wear, this article introduces a laser-assisted ultrasonic vibration dressing technique. Firstly, finite-element simulations were conducted on the dressing process of a bronze-bonded diamond wheel, and the wheel's temperature field distributions under different laser parameters were simulated. By analysing the simulation results of temperature fields and the melting point of the bronze bond, the laser parameters for laser-assisted ultrasonic vibration dressing tests were optimized, and then actual tests were carried out on the bronze-bonded diamond wheel. Results showed that, with appropriate technology parameters, the laser-assisted ultrasonic vibration dressing technique achieved desirable dressing results; specifically, the dressing force was low, the abrasive particles had high protrusions and the wheel had a large chip space and favourable surface topography.